INTERAKSI SOSIAL KOMUNITAS VIRTUAL MEME COMIC INDONESIA - Mestika, Indah; Sudrajat, Ratih Hasanah; Prasetio, Arie (Prodi Ilmu Komunikasi FISIP Universitas Langlangbuana, 2016)
Humans are social beings who have a need to constantly interact with other humans, the presence of the internet, especially social media change the style of interaction that was originally in person can now be done virtually, evenhumans can form a particular group without having to meet directly with each other via social media. Facebook is one of the social media are widely used in Indonesia and form a virtual community. In this study, researchers interested in studying the social interaction of virtual communities on facebook social media. This type of research is qualitative research constructivist paradigm. Method of the approach in this study is a virtual ethnography. Data collection techniques are performed online and offline interviews and observations online at MCI community. Discussion through interviews, while three key respondents of this research is the facebook social media users were active in the MCI and one supporting respondent namely Admin Coordinator. The results showed that there is a motive behind the four Facebook users join and active in the community MCI there are curious motif, entertaining motif, the motif of expression and motif of self-esteem. In addition, varieties of languages are built facebook users in interaction in MCI, researcher has found three points, namely the term greeting, typical expression, and use hashtag. So it can be said that social interaction in a virtual community also has a culture or way of interacting like usual but it is an internet community.